2021
DOI: 10.3389/fnut.2021.718877
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Changes Related to Eating Habits, Physical Activity, and Weight Status During COVID-19 Quarantine in Italy and Some European Countries

Abstract: Novel human coronavirus disease (COVID-19), an infectious respiratory disease, has affected more than 50 million people around the world up to November 2020, thereby becoming the fifth documented pandemic since the Spanish flu in 1918. SARS-CoV-2 virus originated in China and evolved for 4 months within the country before becoming a global threat. There is currently no drug approved by the Food and Drug Administration (FDA) for which efficacy on the virus has been proved. Therefore, the only strategy against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 20 publications
6
23
0
3
Order By: Relevance
“…During Spain's lockdown, the level of PA among our population was lower than usual, in concordance with other studies [51]. Our MHOe population decreased their daily moderate-vigorous PA and increased sedentarism because going to sports centers was not permitted during lockdown.…”
Section: Discussionsupporting
confidence: 91%
“…During Spain's lockdown, the level of PA among our population was lower than usual, in concordance with other studies [51]. Our MHOe population decreased their daily moderate-vigorous PA and increased sedentarism because going to sports centers was not permitted during lockdown.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we believe that the oxidative stress and subsequent release of inflammatory cytokines that accompany SARS-CoV-2 infection could explain the alterations in the ANS in young subjects after COVID-19 in our study. Other factors explaining ANS alterations may also be attributed to behavioral changes during and after infection, such as changes in physical activity [47], nutritional status [48], and food and fluid consumption [49]. These conditions also affect the blood volume (causing hypovolemia) and cardiovascular response [5].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of COVID-19 impacted dietary practices both negatively and positively throughout Europe. Several studies reported an increase in the quality of the diet with increased consumption of healthy foods and increased AMD ( 62 , 63 ). However, the higher quantity of food consumed during the restriction period was associated with other poor lifestyle outcomes, including weight gain and limited physical activity ( 64 ).…”
Section: Discussionmentioning
confidence: 99%